Generation of Hydrogeological Units for 3D Modelling Using Open‐Source Tools in the Mexico Basin - Montaño‐Caro, Juan Camilo; Escolero‐Fuentes, Oscar; Morales‐Casique, Eric (Geoscience data journal, 2025)
ABSTRACT This dataset contains hydrogeological cross‐sections for 3D modelling in the Mexico Basin, developed using Python scripts and GIS tools. The cross‐sections are based on existing geological studies and integrate a variety of lithologies and structural features, including volcanic and sedimentary units. While the dataset provides comprehensive coverage, it does acknowledge limitations in geological and structural resolution due to the availability of data. The dataset includes shapefiles representing hydrogeological units in both line and polygon formats, alongside topographic sections, surface hydrogeological distribution and regional fault systems. Although modifications may be required for specific applications, it serves as a strong foundation for multidisciplinary studies in groundwater and geological modelling. Hosted on open‐source repositories, the data can be easily adapted for use in 3D modelling frameworks like GemPy and FloPy. This dataset is a valuable resource for understanding groundwater dynamics in the Mexico Basin and offers flexibility for future updates as new data become available or project needs evolve. A dataset of hydrogeological sections for the Mexico Basin was developed using Python and GIS, integrating existing geological research. It supports 3D modelling and includes shapefiles for subsurface units, topographic sections, surface distributions and regional faults, allowing for easy adaptation for specific objectives and new data integration.